Simultaneous effect of different chromatographic conditions on the chromatographic retention of pentapeptide derivatives (HGRFG and NPNPT) - Peng, Huan; Yang, Xiangrong; Fang, Huanle; Zhang, Zhongqi; Zhao, Jinli; Zhao, Te; Liu, Jianli; Li, Yan (Frontiers in Chemistry, 2023)
To accurately predict the retention of pentapeptides with analogous structures in chromatography, the retention times of 57 pentapeptide derivatives in 7 buffers at 3 temperatures and 4 mobile phase compositions were measured via reversed-phase high-performance liquid chromatography (RP-HPLC). The parameters (kHA, kA and pKa) of acid-base equilibrium were obtained by fitting the data corresponding to a sigmoidal function. We then studied the dependence of these parameters on the temperature (T), organic modifier composition (φ, methanol volume fraction) and polarity (PNm parameter). The results showed that logkHA and logkA exhibited linear relationships with 1/T, φ or PNm for all pentapeptides, especially for the acid pentapeptides. Based on this, we proposed two six-parameter models with (1) pH and T and (2) pH and φ or PNm as the independent variables. These models were validated for their prediction capacities by linearly fitting the predicted retention factor (k)-value and experimental k-value. In the model of pH and T, the correlation coefficient (R2) of the acid pentapeptides was 0.8603, suggesting a certain prediction capability of chromatographic retention. Moreover, in the model of pH and φ or PNm, the R2 values of the acid and neutral pentapeptides were greater than 0.93, and the average root mean squared error (RMSE) was approximately 0.3, indicating that the k-values could be effectively predicted. In summary, the two six-parameter models were appropriate to characterize the chromatographic retention of amphoteric compounds, especially the acid or neutral pentapeptides, and could predict the chromatographic retention of pentapeptide compounds.